2022
DOI: 10.1101/2022.10.25.513090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 S1 Subunit Booster Vaccination Elicits Robust Humoral Immune Responses in Aged Mice

Abstract: Currently approved COVID-19 vaccines prevent symptomatic infection, hospitalization, and death of the disease. However, the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants raises concerns of reduced vaccine effectiveness and increased risk of infection. Repeated homologous booster in elderly individuals and immunocompromised patients is considered to solve severe form of disease caused by new SARS-CoV-2 variants but cannot protect completely against breakthrough infection. In… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…Protein subunit vaccine approaches against COVID-19 are highly favorable for worldwide equitable distribution due to their low cost per dose, relative thermostability, and excellent safety profile [ 22 , 23 , 24 , 25 ]. Our previously published reports on vaccines against SARS-CoV-1, Middle-East respiratory syndrome coronavirus (MERS-CoV), and SARS-CoV-2 have demonstrated the ability of S1 subunit targeting vaccines to generate neutralizing antibody responses against Beta coronaviruses [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Protein subunit vaccine approaches against COVID-19 are highly favorable for worldwide equitable distribution due to their low cost per dose, relative thermostability, and excellent safety profile [ 22 , 23 , 24 , 25 ]. Our previously published reports on vaccines against SARS-CoV-1, Middle-East respiratory syndrome coronavirus (MERS-CoV), and SARS-CoV-2 have demonstrated the ability of S1 subunit targeting vaccines to generate neutralizing antibody responses against Beta coronaviruses [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted December 14, 2022. ; https://doi.org/10.1101/2022.12.12.520124 doi: bioRxiv preprint chose to focus on the induction of antibodies because they are the hypothesized correlate of protection against severe COVID-19 20 . Furthermore, prior studies have shown the positive correlation and high concordance between binding antibodies and traditional virus-based microneutralization tests 30 . Our past work has also shown the positive correlation between the MSD ACE2 binding inhibition and virus-based microneutralization tests 30 .…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, prior studies have shown the positive correlation and high concordance between binding antibodies and traditional virus-based microneutralization tests 30 . Our past work has also shown the positive correlation between the MSD ACE2 binding inhibition and virus-based microneutralization tests 30 . As a conventional and multiplex test, measurement of competitive immunoassay for quantifying inhibition of the spike-ACE2 interaction can serve as a surrogate for traditional virus-based microneutralization tests with high levels of correlation 41,44,63 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations